The Analysis of Habitat Suitability for Macaca Tonkeana in the Pangi Binangga Natural Reserve of West Toboli Village Using SIG and PCA Approach - Susianti, Siti; Muis, Hasriani; Misrah, Misrah; Akhbar, Akhbar; Arianingsih, Ida; Baharuddin, Rhamdhani Fitrah; Hulu, Amati Eltriman (Advance Sustainable Science, Engineering and Technology, 2024)
The boti monkey, also known by its scientific name Macaca tonkeana, is a type of endemic primate found on Sulawesi Island. This study aims to determine the suitability of Macaca tonkeana habitat by using spatial analysis methods to determine the most suitable areas for survival. The study used a sample of locations conducted by observation method. The data collected was then spatially analysed by overlaying, classing, weighting, and scoring. PCA analysis was used to classify variables and assign weights to each parameter. Based on the habitat suitability model developed, the study sites were classified into three suitability levels: low, medium and high. Low suitability with an area of 9.475621 ha (0.374%). Medium suitability with an area of 461.777729 ha (18.184 %). High suitability with an area of 2065.896076 ha (81.442%). The model validation showed that most of the validation points were located within the high suitability class, with 92.59% of the total validation points. This indicates that the study site is likely to be a highly suitable habitat for Boti Monkeys.